Hepatic bleeding induced by streptokinase and heparin in a patient with acute myocardial infarction - Okoshi, Katashi [UNESP]; Cicogna, Antonio Carlos [UNESP]; Coelho, Kunie Iabuki Rabello [UNESP]; Drumond, Sula Gláucia Lage [UNESP]; Okoshi, Marina Politi [UNESP] (My University, 2002)
Although rare, major bleeding is the most important side effect of thrombolytic therapy in acute myocardial infarction (AMI) (Levine et al., 1995). Spontaneous hepatic bleeding in normal liver after thrombolytic administration has rarely been reported in literature. To our knowledge, there are only three cases of hepatic bleeding related to thrombolytic therapy in AMI. In these, the used drugs were anisolylated plasminogen streptokinase activator complex (APSAC) (Garcia-Jiménez et al., 1997; Fox et al., 1991) and rt-PA (Garcia-Jiménez et al., 1997). We report a case of hepatic bleeding after streptokinase followed by units over 60 minutes). The next day, the patient developed third-degree atrioventricular block and a temporary pacemaker was inserted. Twenty-seven hours after streptokinase infusion, the patient complained of refractory chest pain that was interpreted as post-myocardial infarction angina; clotting screen was normal and intravenous heparin was started (80 U/kg followed by 18 U/kg/hour). After four hours of heparin administration, the patient presented abdominal pain and distension, and his blood pressure and hematocrit level dropped. Abdominal ultrasonography revealed free fluid in the peritoneal cavity (about 3,000 mL). A laparotomy disclosed blood in the abdominal cavity with bleeding from the right lateral hepatic segment, which was removed. The remaining abdominal viscera were normal and there was no other evidence of hemorrhage. The partial liver resection presented subcapsular hemorrhage with small parenchymal hemorrhage. Histopathological examination also revealed focal areas of ischemic centrilobular necrosis. The patient died of multiple organ system failure 21 days after admission. Copyright © 2002 By PJD Publications Limited.
Keywords: Acute myocardial infarction (AMI); Major bleeding; Side effect of thrombolytic therapy; Spontaneous hepatic bleeding; Thrombolytic therapy in AMI; alteplase; anistreplase; heparin; streptokinase; abdominal distension; abdominal pain; acute heart infarction; clinical feature; death; echography; fibrinolytic therapy; histopathology; human; hypotension; laparotomy; liver hemorrhage; multiple organ failure; partial hepatectomy; side effect; thorax pain